Loss of neural crest‐associated gene FOXD1 impairs melanoma invasion and migration via RAC1B downregulation. Issue 11 (29th September 2018) - Wu, Huizi; Larribère, Lionel; Sun, Qian; Novak, Daniel; Sachindra, Sachindra; Granados, Karol; Umansky, Viktor; Utikal, Jochen
Abstract : Recent studies suggest that malignant melanoma heterogeneity includes subpopulations of cells with features of multipotent neural crest (NC) cells. Zebrafish and mouse models have shown that reactivation of neural crest‐specific pathways during transformation determines the invasiveness of melanoma cells. In our study, we show that the neural crest‐associated transcription factor FOXD1 plays a key role in the invasion and the migration capacities of metastatic melanomas both in vivo and in vitro . Gene expression profiling analysis identified both an upregulation of FOXD1 in NC and melanoma cells, as well as a downregulation of several genes related to cell invasion in FOXD1 knockdown cells, including MMP9 and RAC1B . Furthermore, we demonstrate that knockdown of RAC1B a tumor‐specific isoform of RAC1, significantly impaired melanoma cell migration and invasion and could abrogate enhanced invasiveness induced by FOXD1 overexpression. We conclude that FOXD1 may influence invasion and migration via indirect regulation of MMP9 and RAC1B alternative splicing in melanoma cells. Abstract : What's new? One hallmark of melanoma transformation and metastatic dissemination is epithelial‐mesenchymal transition. EMT is controlled by a set of genes which are also involved in neural crest (NC) differentiation during development, and are suspected to influence melanoma cell development and behavior. Using a human differentiation model of the melanocytic lineage to generate human NC cells, the authors identify TWIST1, MSX1 and FOXD1 among the top upregulated genes in both NC and melanoma cells. They demonstrate that the NC‐associated FOXD1‐RAC1b axis is essential for invasion and migration of melanoma cells, and suggest that its downstream target RAC1B may be of therapeutic interest.